THE EFFECT OF REWARD AND JOB SATISFACTION ON THE POLICE PERSONNEL PERFORMANCE IN THE RIAU POLICE HEADQUARTERS - Vita Mayastinasari (Universitas Hayam Wuruk Perbanas, 2013)
This study examined the effect of reward and job satisfaction on the police personnel performance in the Riau Police Headquarters. This involved 12 locations, such as POLDA Riau, POLRESTA Pekanbaru; and 10 Police of Resorts/POLRES (Indragiri Hilir; Indragiri Hulu; Pelelawan; Siak; Bengkalis; Dumai; Rokan Hilir; Rokan Hulu; Kampar; Kuantan Singingi) with number of population was 6,010 personnel. The sampling technique used stratified random sampling. Questionnaires were distributed to612 respondents that consisted of Bintara, First Officer (Pama) and Intermediate Officers (Pamen). The results show that: 1) simultaneously, there was a direct positive effect on the performance of the reward. But partially, on 9 object of research, namely: POLDA Riau; POLRESTA Pekanbaru; and 7 POLRES (Indragiri Hilir; Pelalawan; Siak; Bengkalis; Dumai; Rokan Hilir and Kampar), there was no direct influence of the reward on the performance; 2)and partially and simultaneously, there was a direct and positive effect of job satisfaction on the performance; 3) and partially and simultaneously, there was a positive and direct effect ofreward on job satisfaction; 4) simultaneously, there was an indirect effect of reward towardperformance. However, partially, there was no indirect effect of reward on performance at the Kuantan police station Singingi.